2020
DOI: 10.1093/ve/veaa003
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling virus relationships by structure-based phylogenetic classification

Abstract: Delineation of the intricacies of protein function from macromolecular structure constitutes a continual obstacle in the study of cell and pathogen biology. Structure-based phylogenetic analysis has emerged as a powerful tool for addressing this challenge, allowing the detection and quantification of conserved architectural properties between proteins, including those with low or no detectable sequence homology. With a focus on viral protein structure, we highlight how a number of investigations have utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 159 publications
(191 reference statements)
2
21
0
1
Order By: Relevance
“…Recent structures of the attachment-mediating GP1 glycoprotein from the clade D WWAV have revealed structural diversity within the GP1 of TfR1-tropic viruses [ 25 , 66 ], principally within GP1 loop regions that are likely involved in TfR1 recognition [ 26 ]. Such structural variation across NW mammarenaviruses with shared receptor-tropism may indicate diverse modes of TfR1 recognition [ 67 ]. WWAV-AV96, which was associated with fatal human illness [ 20 ], utilizes hTfR1 for viral entry [ 25 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent structures of the attachment-mediating GP1 glycoprotein from the clade D WWAV have revealed structural diversity within the GP1 of TfR1-tropic viruses [ 25 , 66 ], principally within GP1 loop regions that are likely involved in TfR1 recognition [ 26 ]. Such structural variation across NW mammarenaviruses with shared receptor-tropism may indicate diverse modes of TfR1 recognition [ 67 ]. WWAV-AV96, which was associated with fatal human illness [ 20 ], utilizes hTfR1 for viral entry [ 25 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it has been shown that class II viral glycoproteins have counterparts in cellular proteins, demonstrating the possibility of horizontal gene exchange [ 70 ], and secondly, viral glycoproteins are under environmental selection pressure for the cellular receptors and thus inclined to higher sequence and/or structural variability. This is noticeable when comparing the available structures of the receptor-binding domain (RBD) within the spike glycoprotein S (a class I viral fusogen) across the members of the Coronaviridae family, as shown early this year [ 71 , 72 ].…”
Section: The Open Question Of a Structure-based Classification Of mentioning
confidence: 99%
“…CoV S protein is a key viral factor that primarily shoulders the host cell and species tropism, one of the critical viral properties, and thus, its biologically significant variations would influence much the viral phenotype. Of note here, the structure-based phylogenetic analysis of the receptor-binding S1 domain ( Forni et al, 2017 ; Ng et al, 2020 ) and also the extensive systemic study on the receptor-usage and infection ability to cell types of different species ( Letko et al, 2020a ) have suggested the presence of an unknown receptor(s) for HCoVs. The current seven species of HCoVs are most likely to have appeared through evolution via multiple complicated receptor switching events.…”
Section: Integrative Virology Of Hcovsmentioning
confidence: 99%
“…Many CoVs utilize peptidases as the cellular receptor, despite that their enzymatic domains are not required for the viral entry process ( Fehr and Perlman, 2015 ). It has been reported that the receptor-specific clustering for viral receptor-binding proteins from the family Coronaviridae is absent ( Ng et al, 2020 ), and that there exist many HCoV receptors other than ACE2 ( Fehr and Perlman, 2015 ; de Wilde et al, 2018 ; Ye et al, 2020 ). These reports suggest a complicated evolutionary pathway for HCoVs, which may include the switch to the same receptor on multiple occasions ( Li F. et al, 2005 ; Wu et al, 2009 ; Song et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%